Breaking in [videorecording (DVD)] - Union, Gabrielle; Burke, Billy; Cabral, Richard (Universal Pictures Home Entertainment, 2018)
Shaun Russel's life is thrown into turmoil after her father's unexpected death. She takes her two young children out to his mansion in Malibu in order to attempt to settle his estate. The mansion is designed with state-of-the-art security that ends up trapping her kids inside, along with four criminals who plan to capture her late father's wealth as well. Shaun must now attempt to save her children and defeat the villains.